Pemulihan Hijau Pasca-COVID-19 di Indonesia: Prospek di Tengah Ketergantungan Energi Batu Bara - Alifia Sekar Sriwijaya; Ari Camila Puspa Devi (Jurnal Sentris, 2022)
The COVID-19 pandemic comes not only sweeping the world with the high number of deaths and job losses but also gives warning about the threat of climate crisis. Therefore, many international institutions encourage the government to adopt green recovery to revive the economy as well as prepare for climate change mitigation. The crux of this recovery means transitioning energy from coal sector to renewable one. However, Indonesia still has not found the momentum yet, as the recovery chosen by the government is still heavy on coal subsidies. It indicates that the government still focuses on short-term recovery without considering the principle of sustainability. Alas, this paper would like to deconstruct the reason behind such recovery by the Indonesia government. This paper utilizes qualitative research method and collects data from academic literature reviews. Historical institutionalism will be applied in emphasizing the significance of the institution within the domestic and international political structure as well as in analyzing the role of ideas within the society. This paper found that the opportunity for green recovery to be adopted by the Indonesian government is still small due to several factors: 1) long-established relationship between the government and coal industry; 2) constraining factors from the international political structures towards the efforts to abandon the unsustainable sector; 3) lack of public support from the Indonesian society towards the agenda of green recovery.